|
1) Đặt u = \,\,{\left( {\ln x} \right)^n}\,\,\,\,\, \Rightarrow \,\,\,\,\,du = \,\,\,n{\left( {\ln x} \right)^{n - 1}}\frac{{dx}}{x} dv\,\, = \,\,dx\,\,\,\,\, \Rightarrow \,\,\,\,v = x {I_n} = \left. {x{{\left( {\ln x} \right)}^n}} \right|_1^e - n\int\limits_1^e {{{\left( {\ln x} \right)}^{n - 1}}dx = e - n} {I_n} Ta có: {I_n} = e - n{I_{n - 1}} với mọi n > 1 Áp dụng với số nguyên dương n + 1 ta có : {I_{n + 1}} = e - \left( {n + 1} \right){I_n} (1) Với n = 1 ta có: {I_1} = \int\limits_1^e {\ln x\,dx} Đặt u = \ln x\,\,\, \Rightarrow \,\,\,du = \frac{{dx}}{x} dv\,\, = \,\,dx\,\,\,\,\, \Rightarrow \,\,\,\,v = x Suy ra : {I_1} = \left. {x\ln x} \right|_1^e - \int\limits_1^e {dx} = e - x |_1^e = 1 Áp dụng (1) với n = 1 ta có: {I_2} = e - 2{I_1} = e - 2 Vậy I_2= e-2\\ I_1= 1 và I_{n+1}= e-(n+1)I_n
2) Vì 1 \le x \le e\,\,\,\,\, \Rightarrow \,\,\,0 \le \ln x \le 1 \begin{array}{l} \Rightarrow \,\,\,\,0 \le {\left( {\ln x} \right)^{n + 1}} \le {\left( {\ln x} \right)^n}\\ \Rightarrow \,\,\,\,0 \le {I_{n + 1}}\,\,\,\,\,\,\,\,\,\,\, \le \,\,\,{I_n}\\ \Rightarrow \,\,\,\,0 \le e - \left( {n + 1} \right){I_n}\,\,\,\,\, \Rightarrow \,\,\,\,{I_n} \le \,\,\,\frac{e}{{n + 1}} \end{array} Vậy 0 \le \,\,{I_n} \le \,\,\,\frac{e}{{n + 1}} \mathop {\lim }\limits_{n \to + \infty } 0 = 0 và \mathop {\lim }\limits_{n \to + \infty } \frac{e}{{n + 1}} = 0, suy ra : \mathop {\lim }\limits_{n \to + \infty } {I_n} = 0
|
|
Đăng bài 27-04-12 09:44 AM
|
|